An Innovative Tool To Track The Difficulties Of Adolescents Aged Between 11 And 16 Years Old: R.E.U.S.S.I.T.E. - Riard, Emile-Henri; Wallet, Jean-William; Stavrou, Pilios-Dimitris (Advances in Social Sciences Research Journal, 2016)
Helping academic professionals in the construction of pre-teens and teens professional project is often insufficient to lead to decision making that suit their interests and skills due to availability of only partial data i.e. test or academic behaviors. For these professionals, REUSSITE, is a synthetic tool for detecting problems including all dimensions of the project construction: psychomotor; cognitive, intellectual; psycho-affective and psycho-social. Will be successively discussing in turn: situation of adolescents and academic resources; abbreviated presentation of REUSSITE and its conceptual foundations; means of validation of the tool and an interpretation based on the strategy developed by the students.